Gut tumors in flies alter the taste valence of an anti-tumorigenic bitter compound. - Leung, N.Y.; Xu, C.; Li, J.S.S.; Ganguly, A.; Meyerhof, G.T.; Regimbald-Dumas, Y.; Lane, E.A.; Breault, D.T.; He, X.; Perrimon, N.; Montell, C. (Current Biology, 2024)
The sense of taste is essential for survival, as it allows animals to distinguish between foods that are nutritious from those that are toxic. However, innate responses to different tastants can be modulated or even reversed under pathological conditions. Here, we examined whether and how the internal status of an animal impacts taste valence by using Drosophila models of hyperproliferation in the gut. In all three models where we expressed proliferation-inducing transgenes in intestinal stem cells (ISCs), hyperproliferation of ISCs caused a tumor-like phenotype in the gut. While tumor-bearing flies had no deficiency in overall food intake, strikingly, they exhibited an increased gustatory preference for aristolochic acid (ARI), which is a bitter and normally aversive plant-derived chemical. ARI had anti-tumor effects in all three of our gut hyperproliferation models. For other aversive chemicals we tested that are bitter but do not have anti-tumor effects, gut tumors did not affect avoidance behaviors. We demonstrated that bitter-sensing gustatory receptor neurons (GRNs) in tumor-bearing flies respond normally to ARI. Therefore, the internal pathology of gut hyperproliferation affects neural circuits that determine taste valence postsynaptic to GRNs rather than altering taste identity by GRNs. Overall, our data suggest that increased consumption of ARI may represent an attempt at self-medication. Finally, although ARI's potential use as a chemotherapeutic agent is limited by its known toxicity in the liver and kidney, our findings suggest that tumor-bearing flies might be a useful animal model to screen for novel anti-tumor drugs.